Epidemiology of injuries during judo tournaments - Mooren, J.; von Gerhardt, A. L.; Hendriks, I. T. J.; Tol, J. L.; Koëter, S. (Translational Sports Medicine, 2023)
Objective. To determine the injury incidence proportion, distribution of injuries by anatomical location; injury type; injury severity, time loss; mechanism and situations of injuries; and the relative risk of injuries by gender, age, and weight categories during judo tournaments. Study Design. It is a systematic review. Data Sources. A systematic review of the literature was conducted via searches in PubMed, EMBASE, Web of Science, CINAHL, SPORTDiscus, Google Scholar, and PEDro. Eligibility Criteria. All original studies on the incidence of injuries during judo tournaments were included. Results. Twenty-five studies were included out of the 1979 studies. Using the modified AXIS tool score for quality assessment, seven were rated as having good quality, nine were rated as having fair quality, and four were rated as having poor quality. The injury incidence proportion during tournaments ranged from 2.5% to 72.5% for injuries requiring medical evaluation and 1.1% to 4.1% for injuries causing time loss (i.e., inability to continue game participation). The most commonly reported injury location was the head, followed by the hand, knee, elbow, and shoulder. The most frequent types of injury were sprains, followed by contusions, skin lacerations, strains, and fractures. In judo tournaments, injuries were more often sustained during standing fights (tachi-waza) than in ground fights (ne-waza). Conclusion. The tournament injury incidence proportion ranged from 2.5% to 72.5% for injuries requiring medical attention and 1.1% to 4.1% for injuries causing time loss. The head was the most frequently injured body part, and sprain was the most frequent injury type. However, current reports on injuries during judo tournaments are heterogeneous and inconsistent, limiting our understanding of in-match injury risks. Future studies should utilize the guidelines of the International Olympic Committee consensus meeting statement on the methodological approach to injury reporting. We recommend a judo-specific extension of this statement to fit the unique features of judo sports practice.